O qì do Taoismo antigo Nèij?ng e as dificuldades na transmissão no ocidente / The qì of the Nèij?ng ancient Taoism and the transmission difficulties in the West - Dulcetti Junior, Orley (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2013)
O pensamento chinês da sabedoria taoísta, que se desenvolveu ao longo dos tempos e atingiu maturação no período clássico da China durante os Reinos Combatentes (403-256 a.C.) e Hàn (206 a.C.-229 d.C.), influenciou o pensamento médico na elaboração do livro taoista da medicina antiga chinesa o Clássico Interno do Imperador Amarelo (Huángdì Nèij?ng ou simplesmente Nèij?ng). A noção do qì é tema central no taoismo antigo e na medicina tradicional. Discute-se aqui a evolução do qì nesse contexto, seu valor polissêmico e as dificuldades na transmissão escrita nas traduções ocidentais do Nèijing compilado por Wáng Bing (720 d.C.). Essa obra serviu e serve para se regrar os ensinamentos médicos taoistas na China e nos países de idiomas indo-europeus. Os modelos teóricos de hibridação e neo-figurismo de Lackner, fecundidade cultural de Jullien, intertextualidade de Genette procuram explicar as diferenças culturais, linguístico-filológicas com as dificuldades na transmissão do texto original para as traduções ocidentais do Clássico Interno, que preserva a ancestralidade da sabedoria do Imperador Amarelo. Abstract The wisdom of Chinese Taoist thought, which was developed over time and reached maturity in the classical period in China during the Warring States (403-256 BC) and Hàn, influenced medical thinking in drafting the Taoist book of the ancient Chinese medicine Yellow Emperor's Inner Classic (Huángdì Nèij?ng or simply Nèij?ng). The concept of qì is a central theme in Taoism and traditional medicine. It is discussed here the evolution of qì in that context, its polysemic value and the difficulties in writing transmission in Western translations of the Nèij?ng compiled by Wáng Bing (762 A.D.). This work has served and serves to regulate the Chinese medical teachings in China and Indo-European language countries. The theoretical models of hybridization and neo-figurism of Lackner, Julien’s cultural fecundity, Genette’s intertextuality seek to explain cultural, linguistic-philological differences with the difficulties in the transmission of the original text to the Western translations of the Inner Classic, which preserves the ancestrality of the Yellow Emperor wisdom.